Influence of China's 2009 healthcare reform on the utilisation of continuum of care for maternal health services: evidence from two cross-sectional household surveys in Shaanxi Province - Xiaojing Fan; Meghan Bruce Kumar; Zhongliang Zhou; Ching-Hung Lee; Duolao Wang; Haixia Liu; Shaonong Dang; Jianmin Gao (BMC, 2020)
Abstract Background Continuum of care for maternal health services (CMHS) is a proven approach to improve health and safety for mothers and newborns. This study aims to explore the influence of China's 2009 healthcare reform on improving the CMHS utilisation. Methods This population-based cross-sectional quantitative study included 2332 women drawn from the fourth and fifth National Health Service Surveys of Shaanxi Province, conducted in 2008 and 2013 respectively, before and after China's 2009 healthcare reform. A generalised linear mixed model (GLMM) was applied to analyse the influence of this healthcare reform on utilisation of CMHS. Concentration curves, concentration indexes and its decomposition method were used to analyse the equity of changes in utilisation. Results This study showed post-reform CMHS utilisation was higher in both rural and urban women than the CMHS utilisation pre-reform (according to China's policy defining CMHS). The rate of CMHS utilisation increased from 24.66 to 41.55% for urban women and from 18.31 to 50.49% for rural women (urban: χ2 = 20.64, P < 0.001; rural: χ2 = 131.38, P < 0.001). This finding is consistent when the WHO's definition of CMHS is applied for rural women after reform (12.13% vs 19.26%; χ2 = 10.99, P = 0.001); for urban women, CMHS utilisation increased from 15.70 to 20.56% (χ2 = 2.57, P = 0.109). The GLMM showed that the rate of CMHS utilisation for urban women post-reform was five times higher than pre-reform rates (OR = 5.02, 95%CL: 1.90, 13.31); it was close to 15 times higher for rural women (OR = 14.70, 95%CL: 5.43, 39.76). The concentration index for urban women decreased from 0.130 pre-reform (95%CI: − 0.026, 0.411) to − 0.041 post-reform (95%CI: − 0.096, 0.007); it decreased from 0.104 (95%CI: − 0.012, 0.222) to 0.019 (95%CI: − 0.014, 0.060) for rural women. The horizontal inequity index for both groups of women also decreased (0.136 to − 0.047 urban and 0.111 to 0.019 for rural). Conclusions China's 2009 healthcare reform has positively influenced utilisation rates and equity of CMHS's utilisation among both urban and rural women in Shaanxi Province. Addressing economic and educational attainment gaps between the rich and the poor may be effective ways to improve the persistent health inequities for rural women.